1987
DOI: 10.1073/pnas.84.24.8996
|View full text |Cite
|
Sign up to set email alerts
|

Single-stranded DNA from abutilon mosaic virus is present in the plastids of infected Abutilon sellovianum

Abstract: The leaf mosaic of Abutilon selovianum is caused by abutilon mosaic virus (AbMV), a geminivirus that has a circular single-stranded DNA genome. DNA was isolated from intact plastids of AbMV-infected and noninfected plants. Plastids from infected plants were shown to contain the single-stranded AbMV DNA by Southern-blot hybridization experiments that used a probe made from highly purified AbMV DNA. The possibility of adsorption of AbMV virions or viral DNA onto the plastid envelope was ruled out by several in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Clear evidence for rolling circle replication in geminiviruses has been provided by Stenger et al [42]. There is also compelling evidence that AbMV closely associates with chloroplasts if it does not actually replicate in them [9,10]. These lines of evidence would suggest a geminiviral origin as a phage or bacterial plasmid: it is therefore interesting that Petty et al [31] have shown that a geminivirus CP promoter functions efficiently in E. coli.…”
Section: Evolutionary Implicationsmentioning
confidence: 91%
“…Clear evidence for rolling circle replication in geminiviruses has been provided by Stenger et al [42]. There is also compelling evidence that AbMV closely associates with chloroplasts if it does not actually replicate in them [9,10]. These lines of evidence would suggest a geminiviral origin as a phage or bacterial plasmid: it is therefore interesting that Petty et al [31] have shown that a geminivirus CP promoter functions efficiently in E. coli.…”
Section: Evolutionary Implicationsmentioning
confidence: 91%
“…The role of chloroplasts in the life cycle of plant DNA-viruses needs to be examined. In studies of cellular alterations induced by various geminiviruses in systemically infected plants, dramatic morphological changes in the ultrastructure of chloroplasts were identified, such as vesiculated entities, reduced starch and chlorophyll content, accumulation of fibrillar inclusions, virus-like particles, and vDNA within plastids (Esau, 1933; Jeske and Werz, 1978, 1980a,b; Schuchalter-Eicke and Jeske, 1983; Jeske and Schuchalter-Eicke, 1984; Jeske, 1986; Gröning et al, 1987, 1990; Rushing et al, 1987; Channarayappa et al, 1992). For AbMV it was shown that the severity of chloroplast structure remodeling was dependent on light intensity, and diurnal and seasonal conditions.…”
Section: Plastids and Stromules In Viral Infectionmentioning
confidence: 99%
“…Nevertheless, the detection of vDNA, fibrillar inclusions, or virus-like particles within chloroplasts, suggests other functions of this interplay. Until now, only AbMV vDNA was detected in purified plastids from infected plants (Gröning et al, 1987, 1990). An artificial co-purification was excluded by thermolysin and DNase I treatment.…”
Section: Plastids and Stromules In Viral Infectionmentioning
confidence: 99%
“…There is convincing evidence that several plant virus nucleic acids, and T-DNA from Agrobacterium tumefaciens can become localized in chloroplasts (DeBlock et al 1985;Gröning et al 1987;Schoelz and Zaitlin 1989;Gröning et al 1990;Venkateswarlu and Nazar 1991). However, it is not known whether a vector mediated mechanism might be involved in the transport of these nucleic acids into chloroplasts.…”
Section: Introductionmentioning
confidence: 99%